A systematic review of randomised controlled trials in breast reconstruction - Emma Hansson; Camilla Larsson; Alexandra Uusimäki; Karolina Svensson; Emmelie Widmark Jensen; Anna Paganini (Journal of Plastic Surgery and Hand Surgery)
Background: For preference sensitive treatments, such as breast reconstructions, there are barriers to conducting randomised controlled trials (RCTs). The primary aims of this systematic review were to investigate what type of research questions are explored by RCTs in breast reconstruction, where have they been performed and where have they been published, and to thematise the research questions and thus create an overview of the state of the research field.